Associations of Muscle Size and Density With Proximal Femur Bone in a Community Dwelling Older Population - Yin, Lu; Xu, Zhengyang; Wang, Ling; Li, Wei; Zhao, Yue; Su, Yongbin; Sun, Wei; Liu, Yandong; Yang, Minghui; Yu, Aihong; Blake, Glen Mervyn; Wu, Xinbao; et al. (Frontiers in Endocrinology, 2020)
Background: Muscle weakness and bone fragility are both associated with hip fracture. In general, muscle contractions create forces to the bone, and bone strength adapts to mechanical loading through changes in bone architecture and mass. However, the relationship between impairment of muscle and bone function remain unclear, particularly for the associations of muscle with properties of proximal femur cortical and trabecular bone. The aim of this study was to explore the associations of hip/thigh muscle density (CT attenuation value in Hounsfield units) and size with cortical and trabecular bone mineral density (BMD) of the proximal femur. Materials and Methods: Three-dimensional quantitative computed tomography (QCT) imaging of the lumber, hip and mid-thigh was performed in a total of 301 participants (mean age 68.4±6.1 years, 194 women and 107 men) to derive areal BMD (aBMD) and volumetric BMD (vBMD). From the CT images, cross-sectional area (CSA) and density were determined for the gluteus maximus muscle (G.MaxM), trunk muscle at the vertebrae L2 level and mid-thigh muscle. Multivariate generalized linear models were applied to assess associations. Results: Total hip (TH) aBMD was associated significantly with G.MaxM CSA (men: P=0.042; women: P<0.001) and density (men: P=0.012; women: P=0.043). In women, 0.035 cm2 of mid-thigh CSA (95% confidence interval [CI], 0.014-0.057; P=0.002) increased per SD increase in TH aBMD, but this significance was not observed in men (P=0.095). Trunk muscle density and CSA were not associated with proximal femur BMD. The associations of hip/thigh muscle parameters with femoral neck BMD were weaker than those with trochanter and intertrochanter BMD. Furthermore, compared to muscle density, muscle CSA showed better associations with vBMD. G.MaxM CSA was associated with trochanter (TR) Cort. vBMD in men (β, 19.898; 95% CI, 0.924-38.871; P=0.040) and in women (β, 15.426; 95% CI, 0.893-29.958; P=0.038). Handgrip strength was only associated with TR aBMD (β, 0.038; 95% CI, 0.006-0.070; P=0.019) and intertrochanter aBMD (β, 0.049; 95% CI, 0.009-0.090; P=0.016) in men. Conclusions: We observed positive associations of the gluteus and thigh muscle size with proximal femur volumetric BMD. Specifically, the gluteus maximus muscle CSA was associated with trochanter cortical vBMD in men and women.